Global solution of the critical Burgers equation in N Dimensions. (15th July 2017) - Ru, Shaolei; Chen, Jiecheng
Abstract: In this paper, we first prove the local well-posedness of the fractional Burgers equations in N Dimensions. Combining the local well-posedness and the method of modulus of continuity, we show the global well-posedness of the N-D critical Burgers equation in critical Besov spaces B ̇ p, 1 N p ( R N ) with p ∈ [ N, ∞ ) .